Risk of Intracranial Hemorrhage With Concomitant Use of Antidepressants and Nonsteroidal Anti-inflammatory Drugs: A Nested Case-Control Study. Issue 8 (August 2021) - Hou, Po-Cheng; Lin, Fang-Ju; Lin, Shin-Yi; Hwang, Tzung-Jeng; Wang, Chi-Chuan
Background: Whereas previous studies found that concomitant antidepressant and nonsteroidal anti-inflammatory drug (NSAIDs) use may increase the risk of gastrointestinal bleeding, either drug alone increases the risk of intracranial hemorrhage (ICH). Objective: To assess the risk for ICH in patients on concomitant treatment with antidepressants and NSAIDs. Methods: This was a nested case-control study using national insurance claims data in Taiwan between 2005 and 2013. Drug exposure was measured and compared during 3 time windows: 1 to 30, 31 to 60, and 61 to 90 days before the index date, which is the date of the ICH event. Both traditional and newer-generation antidepressants were considered in this study. Results: Patients exposed to both antidepressants and NSAIDs 1 to 30 days before the index date presented a 50% increased odds of developing ICH (OR: 1.53; 95% CI: 1.31-1.80) compared with patients receiving antidepressants alone. Specifically, the concomitant use of nonselective NSAIDs and antidepressants increased these odds compared with antidepressants alone (OR: 1.56; 95% CI: 1.31-1.84), but using a selective cyclooxygenase-2 inhibitor with antidepressant did not alter ICH risk. Regarding antidepressant class, newer-generation antidepressants generally increase the odds of developing ICH by 60% when used concomitantly with NSAIDs. Conclusion and Relevance: Our results suggested that the concomitant use of antidepressants and NSAIDs was associated with an increased odds of developing ICH. NSAIDs, especially nonselective NSAIDs, and serotonergic antidepressants played an important role in this risk. Given the prevalent use of these 2 classes of drugs, this potential drug interaction deserves more attention.